2019
DOI: 10.1186/s12610-019-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

Testicular expression of long non–coding RNAs is affected by curative GnRHa treatment of cryptorchidism

Abstract: BackgroundCryptorchidism is a frequent endocrinopathy in boys that has been associated with an increased risk of developing testicular cancer and infertility. The condition is curable by combined surgery and hormonal treatment during early pre-pubertal stages using gonadotropin releasing hormone agonist (GnRHa). However, whether the treatment also alters the expression of testicular long non-coding RNAs (lncRNAs) is unknown. To gain insight into the effect of GnRHa on testicular lncRNA levels, we re-analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
10
0
1
Order By: Relevance
“…A study on azoospermia in cryptorchidism shows that gonadotropin-releasing hormone agonist treatment of cryptorchidism affects the expression of lncRNA in the testis. In this study, it is confirmed that LINC-ROR, LINC00221, LINC00261, LINC00282, LINC00293, LINC00303, LINC00898, LINC00994, LINC01121 and LINC01553 may play a role in the early stage of spermatogonial stem cell development ( 76 ).…”
Section: Lncrnasupporting
confidence: 73%
“…A study on azoospermia in cryptorchidism shows that gonadotropin-releasing hormone agonist treatment of cryptorchidism affects the expression of lncRNA in the testis. In this study, it is confirmed that LINC-ROR, LINC00221, LINC00261, LINC00282, LINC00293, LINC00303, LINC00898, LINC00994, LINC01121 and LINC01553 may play a role in the early stage of spermatogonial stem cell development ( 76 ).…”
Section: Lncrnasupporting
confidence: 73%
“…SH3BP5‐AS1 is significantly upregulated in neuroblastoma [29]. MTOR‐AS1 is associated with cryptorchidism [30]. RPS6KA2‐AS1 is considered a potential biomarker of acute stroke and is involved in the neurotrophin signaling pathway [31].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptorchidism is an endocrinopathy considered as an important cause of male infertility [42]. The current study evaluated the effects of aqueous and methanolic extracts of R. apetalus on various reproductive (organ weights, spermatozoa parameters, testicular proteins, sex hormones, fertility potential and morphometric characteristics of testis) and metabolic (oxidative stress markers) parameters in unilateral induced cryptorchid rats.…”
Section: Discussionmentioning
confidence: 99%